Structural and electronic properties of self-assembled supramolecular grid structures: Doping of supramolecular thin films - Hassmann, Jörg; Hahn, C. Y.; Waldmann, Oliver; Volz, Eduard; Schleemilch, H-J.; Hallschmid, Nikolaus; Müller, Paul; Hanan, Garry Shawn; Volkmer, Dirk; Schubert, Ulrich S.; Lehn, Jean-Marie; Mauser, Harald; et al. (Materials Research Society Symposium - Proceedings, 1998)
Thin films of self-assembled supramolecular grid structures were prepared by electrochemical deposition. The surface structure of the films was determined by electrochemical in-situ scanning tunneling microscopy (STM), revealing ordered monolayers of the grid molecules on a Au(111) surface. The electronic structure of the films was studied by photoelectron spectroscopy. The thin films show semiconducting behavior with an insulating gap of ca. 2.5 eV. The size of insulating gap can be reduced to 0.5 eV by doping the films with additional Cd ions, which is in agreement with molecular orbital calculations. Additionally, conductivity measurements were performed. By doping of the thin films, their conductivity could be increased by several orders of magnitude. This is due to additional electronic states in the insulating HOMO-LUMO gap, which is confirmed by UPS measurements.